The relationship between religiosity and depression among muslim university students - Dzainal, Noor Dahiah Sulhana; Abdul Aziz, Abdul Rashid (GADING Journal for the Social Sciences, 2023)
Depression is a debilitating illness and has become a major cause of morbidity worldwide. Depression is one of the most prominent cases of mental disorders at this point. According to the World Health Organization (WHO), it affects nearly 350 million people. It is reported that in 2020, depression is the second most debilitating disorder. The main cause of suicide is depression. Therefore, the purpose of this study is to examine the relationship between religiosity and depression among Muslim university students. This is a quantitative study using descriptive and inferential analysis through the use of Statistical Package of Social Science (SPSS) software version 21. The Muslim Daily Religiosity Assessment Scale (MUDRAS) was used to identify religious practices owned by students. In addition, the Depression, Anxiety and Stress Scale (DASS) was used to determine the level of student depression. A total of 200 Muslim students were selected as respondents in the study through a simple random sampling method. The results of the study showed that the majority of students have moderate religious practices and most of them experienced severe level of depression. The correlation test showed that there was a significant negative relationship between religiosity and depression (r=-.242). In conclusion, with good religious practices among student, it can help them to deal with the symptoms of depression. Therefore, parents and the university body should be aware and take appropriate steps in further increasing the level of Islamic comprehension and practices in each student.